Representation of the Father’s Silent Treatment in the Film Dear Nathan: A Roland Barthes Semiotic Analysis - MUHAMMAD BUCKY Al Farizi; Leili Kurnia Gustini (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
ABSTRACT This study aims to examine the representation of the father’s silent treatment in the film Dear Nathan, as well as to reveal the meanings constructed through this communication pattern. The research employs a qualitative method with a semiotic analysis approach. The analysis is based on the framework of denotation, connotation, and myth to interpret selected scenes that depict interactions between Nathan and his father. Data were collected through documentation techniques by repeatedly watching and observing relevant scenes, as well as identifying visual signs, verbal expressions, and cinematographic elements that represent silence as a form of communication. The analysis focuses on how these signs construct meaning within the narrative of the film. The results show that the father’s silent treatment is not merely an act of remaining silent or refusing to speak, but contains symbolic meanings such as emotional distance, authority, disappointment, and control within the family structure. At the level of myth, the film reflects and simultaneously reproduces an ideology that portrays the father as a firm figure with minimal emotional expression. This study concludes that film plays a role in constructing and naturalizing certain patterns of family communication while also opening space for critical reflection on their emotional impact. Keywords: film analysis, father figure, masculinity, representation, semiotics, silent treatment.